2017
DOI: 10.4317/jced.53620
|View full text |Cite
|
Sign up to set email alerts
|

Tensile strength and impact strength of color modified acrylic resin reinforced with titanium dioxide nanoparticles

Abstract: BackgroundPoor mechanical properties are among the main limitations of acrylic resins. Addition of titanium dioxide (TiO2) nanoparticles to acrylic resin has been shown to improve its mechanical properties with an adverse effect on its color. Thus, this study sought to assess the tensile and impact strength of a color modified heat cure acrylic resin reinforced with TiO2 nanoparticles.Material and MethodsIn this in vitroexperimental study, 1wt% TiO2 nanoparticles were added to SR Triplex Hot heat-cure acrylic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 16 publications
1
38
1
2
Order By: Relevance
“…5). Stress concentration results are summarized in Table 2 [17,[35][36][37][38][39][40]. This finding suggests that the higher the stress concentration ratio the best is the stress distribution.…”
Section: Resultsmentioning
confidence: 99%
“…5). Stress concentration results are summarized in Table 2 [17,[35][36][37][38][39][40]. This finding suggests that the higher the stress concentration ratio the best is the stress distribution.…”
Section: Resultsmentioning
confidence: 99%
“…In recent studies, TiO 2 nanoparticles were used to reinforce acrylic resins; however, it was simultaneously reported to cause color changes . Ghahremani et al modified acrylic resins with color pigments after the addition of TiO 2 nanoparticles. In our study, visible opacity was observed in specimens containing 5% TiO 2 nanoparticles.…”
Section: Discussionmentioning
confidence: 99%
“…Khalaf [20] found that acrylic resins added to siwak powder with different percentages can increase flexural strength, but decrease the tensile strength, impact strength, and surface roughness. Ghahremani [21] found that there was an increase in tensile and impact strength on acrylic resins reinforced with nanoparticle titanium oxide.…”
Section: Resultsmentioning
confidence: 99%